Isolation, Characterisation and Vitamin B12 Production Optimization of P. freudenreichii from Turkish Traditional Kars Gravyer - Kavak, Akif Emre; Alimoglu, Zerya Beyza; Ozdemir, Akin; Dertli, Enes (MDPI, 2025)
In this study, nine different Propionibacterium freudenreichii strains were isolated from Kars Gravyer produced by traditional methods in Turkey and identified by sequencing the 16S-23S intergenic region using species-specific primers. The isolated strains were examined in vitro for the presence of the beta-galactosidase enzyme, autoaggregation ability, sensitivity against eight selected antibiotics and survivability under harsh conditions in order to determine their potential probiotic properties. After probiotic potentials were evaluated, an experimental design was made to optimize the production of vitamin B12 in a 3 L glass bioreactor P. freudenreichii NUV774. While all strains showed similar resistance (92-98%) to gastric juice (0.3% pepsin, pH 3.0), they showed resistance to intestinal fluid (0.1% pancreatin, 0.3% bile salt, pH 8.0) between 60% and 92%. It was determined that the viability after 3 and 6 h of incubation in 0.5% and 1% bile salt differed between strains. All isolates exhibited resistance to ciprofloxacin, ampicillin, and trimethoprim-sulphamethoxazole; however, most were sensitive to ofloxacin. Overall, P. freudenreichii strains showed resistance to the gastrointestinal tract, tolerance to pH 3.0, and high tolerance to bile salts. As a result of optimization, maximum vitamin B12 production was found to be 156.8 mg/L. The optimum operating conditions were calculated as temperature = 36.9 degrees C, aeration = 2.430 vvm, and agitation = 159.120 rpm. Hence, P. freudenreichii, as future probiotic strain candidates, will offer an alternative source to Lactobacillus, Bifidobacterium and some Bacillus spp. In addition, this study denoted that the alteration of the production of active vitamin B12 by P. freudenreichii occurs in a strain-dependent manner.
Keywords: dairy propionibacteria; Propionibacterium freudenreichii; vitamin B12; optimization; probiotic properties; LACTIC-ACID BACTERIA; IN-VITRO; ANTIBIOTIC-RESISTANCE; PROPIONIC-ACID; IDENTIFICATION; PROBIOTICS; TOLERANCE; STRAINS; MILK; Biotechnology & Applied Microbiology; Food Science & Technology